Microbiological assessment on water quality consumed by community in Jeli, Kelantan - Mohamad Syahid Farhan Mohd Zaki (2022)
The purpose of this study was to investigate bacterial assessment in the water consumed by community of Jeli, Kelantan. E, coli, Salmonella spp., coliform was usually found in water which have been contaminated. Bacterial from ten different water source of two types of water sample of hill water and ground water were isolated and identified for possible bacteria. The isolated bacteria from water sample were grown on selective agar of MacConkey agar, XLD agar and VRB agar were used to isolate E. colt, Salmonella spp. and coliform. The isolated colonies grown on the selective agar were identified using gram staining and biochemical test of catalase test and TSI test. Three water sample from ground water and three water sample form hill waters have been identified containing E colt. Salmonella spp. were identified in three hill water sample and two round water sample. Three water sample from and water and one from hill water sample were identified containing coliform in the water. lit of ground water sample contain the highest total plate count with 2.44 x I04 efultnL. The sane of E. colt, Salmonella App. and colifomi in the water sample of hill water and pound tier indicates the source or storage of the water has already been contaminated unknowingly intentionally.